Veterinarian nominated common conditions of rabbits and guinea pigs compared with published literature - Robinson, Natalie J.; Lyons, Emma; Grindlay, Douglas; Brennan, Marnie L. (MDPI, 2017)
Rabbits and guinea pigs are increasingly popular pets in the UK, yet little is known about their common ailments, or how these relate to what appears in the published literature. The aim of this study was to characterise the common conditions of rabbits and guinea pigs, and to compare these with the topics found in the published literature. Information about the common conditions seen in rabbits and guinea pigs in clinical practice was obtained from a survey of UK veterinarians. The common conditions seen were compared with results from a structured literature search. Conditions relating to the dental (29.9%), and skin (37.6%) body systems were commonly nominated by veterinarians for rabbits and guinea pigs, respectively. A total of 655 rabbit and 1086 guinea pig citations were examined and there appeared to be a mismatch between the conditions nominated in the veterinary questionnaire, and those found in the literature. This is the first time that the published literature has been compared to the nominated caseload of veterinarians in practice, and there is concern that the literature about rabbits and guinea pigs may not be representative of, or relevant to the caseload seen in clinical practice. This is of importance for clinicians being able to apply an objective, evidence-based approach. The publishing of clinically-relevant, research-based evidence should be prioritised.